Sick to death and not going to take it anymore! : reforming health care for the last years of life - Lynn, Joanne, 1951- (Berkeley, Calif. : University of California Press ; New York : Milbank Memorial Fund, 2004)
Just a few generations ago, serious illness, like hazardous weather, arrived with little warning, and people either lived through it or died. In this important, convincing, and long-overdue call for health care reform, Joanne Lynn demonstrates that our current health system, like our concepts of health and disease, developed at a time when life was mostly short, serious illnesses and disabilities were common at every age, and dying was quick.
Just the facts: serious chronic disease in the last phase of life -- Seeing the world differently: ideas to shape reform -- Good care for some people, sometimes -- Surveying the terrain: opportunities and challenges -- Good care for us all: building the care system to count on.
Includes bibliographical references (pages 167-189) and index.
Print version record.
JSTOR
Keywords: Older people -- Medical care -- United States; Older people -- Long-term care -- United States; Chronically ill -- Medical care -- United States; Terminal care -- United States; Health care reform -- United States; Chronic diseases; Hospice care; Terminal care; Health care reform; Long-term care of the sick; Older people; Chronic Disease; Terminal Care; Health Care Reform; Health Services for the Aged; Long-Term Care; Aged; United States; Hospice Care; Aged, 80 and over; Personnes âgées -- Soins médicaux -- États-Unis.; Personnes âgées -- Soins de longue durée -- États-Unis.; Soins en phase terminale -- États-Unis.; Services de santé -- Réforme -- États-Unis.; Maladies chroniques; Soins en phase terminale; Services de santé -- Réforme.; Soins de longue durée.; Personnes âgées.; elderly; HEALTH & FITNESS -- Health Care Issues; MEDICAL -- Public Health; MEDICAL -- Health Policy; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Diseases; MEDICAL -- Health Care Delivery; Older people; Long-term care of the sick; Hospice care; Chronic diseases; Chronically ill -- Medical care; Health care reform; Older people -- Long-term care; Older people -- Medical care; Terminal care; United States